Microstructure, corrosion and wear properties of FeCrNiMo based coating produced on AISI 1040 steel by using laser coating technique - Islak, Serkan; Ozorak, Cihan (Hitit University, 2018)
This study aims to investigate microstructure, hardness, corrosion and wear properties of FeCrNiMo-based coating produced on AISI 1040 steel by using laser welding method. Microstructure properties and phase formation were examined by SEM-EDS and XRD. The hardness measurement was made by using a microhardness device along a line from the upper surface of the coating to the substrate. The wear tests of both the substrate and coating layer were made with a scratch test device. SEM examinations showed that the coating layer had a dendritic microstructure and was uniformly bonded to the substrate. The coating layer was harder than the substrate. According to wear tests, the friction coefficient of the coating layer was lower compared to the substrate. Substrate and coating layer were immersed in an aqueous solution of %3,5 NaCl for potentiodynamic measurements. Corrosion results showed that coating of the AISI 1040 steel with FeCrNiMo increased the corrosion resistance.
Keywords: wear; corrosion; microstructure; Laser coating; microstructure; wear; corrosion; TA1-2040; laser coating; Engineering (General). Civil engineering (General)